Digital signal processing - Rawat, Tarun Kumar (Oxford University Press, 2015)
"Digital Signal Processing is a comprehensive textbook designed for undergraduate and post-graduate students of engineering for a course on digital signal processing. Following the book's step-by-step approach, students can quickly master the fundamental concepts and applications of DSP. Each topic is explained lucidly through illustrations and solved examples. Divided into 17 Chapters, this text presents the introductory topics such as discrete-time signals and systems, sampling and quantization, convolution, discrete-time Fourier series, discrete-time Fourier transform, and z-transform in a rigorous fashion. Further, topics such as DFT, FFT, filter concepts, filter structures, FIR filter design and IIR filter design are dealt in detail. It also covers the advanced topics such as finite word length effects, multirate DSP, optimum linear filters, and spectrum estimation techniques he chapters are packed with numerous illustrations, solved examples, multiple choice questions, numerical exercises and MATLAB programs. Additional solved examples at the end of the book will provide some more practice to students." -- Publisher's website.